2020
DOI: 10.1177/2377960820963764
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment in Clinical Practice—A Cross-Sectional Study Among Nurses and Nursing Students in Sub-Saharan Africa

Abstract: Introduction Sexual harassment (SH) at the workplace is a globally discussed topic and one deserving of scrutiny. It is an issue that is often avoided although around 25% of nurses worldwide have experienced some form of SH at their workplace. Consequences of SH at workplaces can be very serious and an occupation hazard for nurses around the world. In Sub-Saharan Africa there is also a need for more studies in the field. Objective The overall aim was to determine the prevalence, types, and consequences of sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…This refers to the psychological problems nurses face because of the negative consequences of sexual harassment in the workplace. Several studies, including this one, have found that sexual harassment can have negative psychological effects such as mental health disorders ( Nielsen et al, 2010 ; Ali and Ezz El Rigal, 2019 ), sadness, shame, and anger ( Tollstern Landin et al, 2020 ). Psychological imbalances can cause severe negative emotions and fear in nurses ( Nielsen et al, 2017 ; Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This refers to the psychological problems nurses face because of the negative consequences of sexual harassment in the workplace. Several studies, including this one, have found that sexual harassment can have negative psychological effects such as mental health disorders ( Nielsen et al, 2010 ; Ali and Ezz El Rigal, 2019 ), sadness, shame, and anger ( Tollstern Landin et al, 2020 ). Psychological imbalances can cause severe negative emotions and fear in nurses ( Nielsen et al, 2017 ; Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kahsay et al (2020) , the frequency of sexual harassment among nurses ranges from 10 to 87.5%, with patients (46%) being the most common source. Tollstern Landin et al (2020) discovered that in Tanzania, Africa, nearly 10% of nurses and nursing students were sexually harassed, with “sexual jokes and comment” (61.3%) and “unwelcome touching and hugging” (61.3%) being the most common forms of sexual harassment (48.4%). The study also revealed that sexual harassment in the workplace could be extremely dangerous, posing a serious job risk and stigma for nurses ( Tollstern Landin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, research articles have shown that female nurses compared with male nurses disproportionally deal with sexual harassment in clinical settings, with figures showing an increasing trend. 23 This study aims at filling this crucial gap and exploring the prevalence of sexual harassment of female nurses in the Greek NHS and the frequency of reporting/not reporting sexual harassment.…”
Section: Introductionmentioning
confidence: 99%